“What about Newspapers?”. Some Refl ections on Asia, Language Barriers, and Human Rights Education in Higher Education Institutions in (Eastern) Asia .......... 421` - Smith, Rhona K.M. (Promoting Changes in Times of Transition and Crisis: Reflections on Human Rights Education, 2013)
Developing human rights education in universities in China has been a major national task, supported by a range of overseas partner institutes and donor organisations. How-ever, advancements made in China have been aided by the availability of source material in Chinese, particularly online (for example, through www.ohchr.org). Similar materials are not available in other Asian languages. This gives rise to significant problems when seeking to establish human rights education initiatives particularly in higher education institu-tions. This paper seeks to analyse the relevant issues and present some personal reflections on ways forward.  Pedagogic and academic literature on curriculum and learning development will in-form the initial section of the paper, establishing threshold requirements for teaching hu-man rights at higher education institutions. Inevitably there are limitations based on the available paper and electronic resources. Viewed in the context of human rights education, the issue is more acute. Human rights education is, of course, predicated on universalism of human rights. The literature makes clear the need for human rights education and the fact it should conform to the “4As” of education and other rights (i.e. it should be available, accessible, acceptable and adaptable). At higher education this presents problems when the materials are available in limited languages; not all States and/or National Human Rights Institutions translate all pertinent UN documentation, for example, into national languag-es. NGOs and civil society offer a partial solution through local translations of treaties and UN reports. This language issue is more acute in higher education when access to primary source material is required. However, even if the primary source material is available in ap-propriate languages, a lack of access to academic commentary thereon, suitable textbooks and support materials remains. There are many factors limiting availability of these materi-als including internal capacity.This paper will offer some reflections on the experience of the author in working with institutions, particularly China and Southeast Asia, developing capacity to offer human rights courses in higher education institutions. A partial solution of focussing on skills and attitude (from the hand, heart, head model of human rights education) will be discussed. Newspapers and materials drawn from popular culture and indeed tradition can be used as a base for teaching and learning initiatives, promoting a practical approach to human rights education which respects the principles underpinning the concept. It will be argued that high quality learning can thus be delivered with a minimum of academic sources.